Fundamentals of microfabrication and nanotechnology. - Madou, Marc J. (CRC Press, 2012)
"In Solid State Physics, Fluidics and Analytical Techniques in Micro- and Nanotechnology we lay the foundations for a qualitative and quantitative theoretical understanding of micro-and nano-electromechanical systems, i.e., MEMS and NEMS. In integrated circuits (ICs), MEMS and NEMS, silicon (Si) is still the substrate and construction material of choice"--